2022
DOI: 10.1186/s12872-022-02578-w
|View full text |Cite
|
Sign up to set email alerts
|

Strain-based discoordination imaging during exercise in heart failure with reduced ejection fraction: Feasibility and reproducibility

Abstract: Purpose Various parameters of mechanical dyssynchrony have been proposed to improve patient selection criteria for cardiac resynchronization therapy, but sensitivity and specificity are lacking. However, echocardiographic parameters are consistently investigated at rest, whereas heart failure (HF) symptoms predominately manifest during submaximal exertion. Although strain-based predictors of response are promising, feasibility and reproducibility during exercise has yet to be demonstrated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Incorporation of exercise parameters may further improve patient selection, but these are not yet part of routine clinical decision making for CRT. 5 However, several studies showed a positive relationship between pre-implantation maximal exercise capacity (peak oxygen uptake; VO 2 peak) and CRT response, 6 7 suggesting that more severely impaired HF patients are less likely to achieve an echocardiographic response. This may be because their exercise capacity is more severely limited by peripheral derangements.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Incorporation of exercise parameters may further improve patient selection, but these are not yet part of routine clinical decision making for CRT. 5 However, several studies showed a positive relationship between pre-implantation maximal exercise capacity (peak oxygen uptake; VO 2 peak) and CRT response, 6 7 suggesting that more severely impaired HF patients are less likely to achieve an echocardiographic response. This may be because their exercise capacity is more severely limited by peripheral derangements.…”
Section: Introductionmentioning
confidence: 99%
“…A barrier for the widespread implementation of assessment of maximal exercise capacity is that symptom limiting exercise testing is burdensome, and often not truly achievable for patients with severe HF. 5 8 Therefore, ‘submaximal’ exercise testing could be a valuable alternative. One of the submaximal exercise parameters that reflect exercise capacity are oxygen kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations